Mathematics Creative Thinking Skills Reviewed from the Students’ Self-Confidence by Implementing the Treffinger Learning Model Assisted by Geogebra (Journal of Primary Education, 2020)
Creativity and self-confidence play important roles in learning mathematics. Treffinger learning model was believed to facilitate the strengthening of both aspects. This learning model theoretically will be more meaningful if it is supported by software that can help visualize the mathematics concept. That choice is the Geogerbra software. This research aimed to describe the mathematics creative thinking skills reviewed from self-confidence aspects of 7th grade students. The study was mixed-methods research with a sequential explanatory design. There were 30 students involved in this study. They were taken based on three self-confidence categories: high, moderate, and low level. The quantitative data collection technique used creative thinking test and the qualitative data collection techniques were questionnaire and interview. The findings shown that (1) the learning outcome by implementing Treffinger assisted by Geogebra was effective, (2) in terms of mathematics creative thinking skills process aspect, the students with high self-confidence could master all indicators well. Students with moderate self-confidence only could master three aspects. They were fluency, flexibility, and elaboration. The low self-confidence students only mastered fluency and elaboration aspects. Based on the findings, it can be concluded that Treffinger learning model could improve the students' mathematics creative thinking skills reviewed by their self-confidence.